Effect of microwave sintering on microstructure and mechanical properties in Y-TZP materials used for dental applications. Issue 5 (June 2015) - Presenda, Álvaro; Salvador, María D.; Peñaranda-Foix, Felipe L.; Moreno, Rodrigo; Borrell, Amparo
Abstract: The aim of this work is to study the application of microwave sintering to consolidate yttria-stabilized zirconia polycrystalline (Y-TZP) ceramics commonly applied in dentistry, so as to obtain highly dense materials and fine microstructure with shorter sintering cycles. Three Y-TZP materials are considered: two commercially available for dental applications and one laboratory studied powder. Microwave sintering was carried out at 1200 and 1300 °C for 10 min and conventional sintering at 1300 and 1400 °C for 2 h. Relative density, Vickers hardness and fracture toughness values for sintered samples were determined. Microwave sintering results, generally, in improved mechanical properties of the materials in terms of hardness and fracture toughness compared to conventional sintering and, in some cases, at lower sintering temperatures. A finer grain microstructure (final grain size<250 min) was obtained with microwave sintering for both commercial materials. Fracture toughness values differ significantly between sintering techniques and chosen parameters. These results suggest that microwave heating can be employed to sinter Y-TZP commercial ceramics for dental applications obtaining improving the mechanical properties of the materials with a very important time and energy consumption reduction.